(3eUHGM GdCfGe aj TQM TQGjY GdESdGes - (3GdHOjQj GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhdg cJGH GdTQcI hGdfXQ aj aUhd ; GdChd aj CbSGegG GdTQcI GLJeGY Mbhb Gdedc aj GdTjA GdhGMO Ydi SHjd GdGdTjGY Ke GdeTJQc bO jchf YjfG hbO jchf (B... (3hbO jchf MbG hSHH GdTQcI (B...s
(3BNQgG (B:s
.... (3GdGLJeGY Ydjg haj GdLhGgQ GdGLJeGY HbSejg Ydjg hcja cGf adhdG GdGLJeGY dCecf Gdbhd HGdUMI dHYV GdYeheGJ ceG GYJQa HPdc GdeMbb GdEQOHjdj aj eLeY GdHQgGf (B... (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3Gd`CYdGe (B2/121s
(3GdPQjYI (B21 / 68 ( 4132)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis